Solar flare impact on FUV based thermospheric O/N2 estimation. (September 2016) - Zhang, Y.; Paxton, L.J.; Kil, H.
Abstract: During/after intense solar flares, FUV based thermospheric O/N2 ratio decreases and recovers instantly, indicating that the decrease is not physical. Simulations with an increased solar X-ray (0–10 nm) flux and a fixed O and N2 profiles show a significant 135.6 nm/LBHS decrease that is sufficient to explain the O/N2 decrease. The false O/N2 decrease is mostly due to increased differences in O2 absorption at 135.6 nm and LBHS caused by low-altitude emissions associated with enhanced X-rays. However, the heating from solar flares may cause a weak depletion in O/N2 . Highlights: Thermospheric O/N2 depletion anomaly during intense solar flares. The O/N2 anomaly is mostly caused by enhanced X-ray during flares. Provide a recommendation to correct the flare time O/N2 estimation based on FUV data.